Effects of cadmium stress on seed germination and physiological-biochemical characteristics in okra: a comparative study of red and green varieties - Wanwan Wang; Lei Yu; Xuexia Zhang; Jingbo Yu; Zhou Jiang; Long Xu; Haiyun Rui (PeerJ)
Previous study has demonstrated that okra (Abelmoschus esculentus (L.) Moench) is capable of accumulating cadmium (Cd) in both plants and fruits. However, there is still little known about the physiological responses of different okra cultivars to Cd accumulation. This study investigated the effects of exogenous Cd application on various growth parameters and physiological aspects in two okra varieties (red and green okra). The results indicated that Cd exposure had a dose-dependent inhibitory effect on seed germination rate and potential. Addition of 50 µM Cd to the hydroponic solution led to a significant reduction in plant biomass. In the red okra variety, Cd accumulation peaked at 287.8 mg kg−1 DW in shoots and 790.3 mg kg−1 DW in roots, while in green okra, these values reached 280.8 mg kg−1 DW in shoots and 903.7 mg kg−1 DW in roots. Furthermore, the Cd treatment resulted in an increase in chloroplastic pigment content of both okra varieties. Production of superoxide anion (O2•−) and hydrogen peroxide (H2O2) significantly rose in the roots of both varieties, with O2•− levels increasing by 298.8% in red okra and 505.8% in green okra roots, and H2O2 levels increasing by 2.23-fold in red okra and 1.4-fold in green okra roots. This rise in reactive oxygen species led to elevated proline content (3.09-fold in red okra roots and 8.45-fold in green okra roots) and non-protein sulfhydryl (NPSH) levels (13.52-fold in red okra roots and 10.21-fold in green okra roots), as well as increased activities of peroxidase (POD) and superoxide dismutase (SOD). Notably, green okra exhibited a more efficient antioxidant defense system and greater tolerance to Cd-induced oxidative stress compared to red okra. This study provides a foundation for developing Cd-tolerant crop varieties and improving phytoremediation strategies.